The Effect of Job Involvement and Career Development on Work Motivation of Civil Servants at the Department of Public Housing, Settlement Areas, and Environment of Ketapang Regency - Siti Citra Lestari; Eru Ahmadia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of Job Involvement and Career Development on the Work Motivation of Civil Servants at the Department of Public Housing, Settlement Areas, and Environment of Ketapang Regency. The study employed a quantitative approach with an associative method. The population consisted of all Civil Servants at the Department of Public Housing, Settlement Areas, and Environment of Ketapang Regency in 2025, totaling 69 employees. A census sampling technique was applied, in which the entire population was used as the research sample. Data analysis included validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that all research instrument items are valid and reliable. The regression model produced the equation Y = 1.517 + 0.339X1 + 0.290X2. The correlation coefficient value is 0.519, indicating a moderate relationship between Job Involvement and Career Development and Work Motivation. The coefficient of determination is 26.9%, meaning that Work Motivation can be explained by Job Involvement and Career Development, while the remaining 73.1% is influenced by other variables not included in this study. The simultaneous test results show that Job Involvement and Career Development jointly have a significant effect on Work Motivation. The partial test results demonstrate that Job Involvement has a significant effect on Work Motivation and that Career Development also has a significant effect on Work Motivation among Civil Servants at the Department of Public Housing, Settlement Areas, and Environment of Ketapang Regency.